Synchronized oscillations caused by disinhibition in rodent neocortex are generated by recurrent synaptic activity mediated by AMPA receptors - Castro-Alamancos, Manuel A (Blackwell Science Inc, 2002)
During disinhibition the neocortex generates synchronous activities. In neocortical slices application of GABA(A) and GABA(B) receptor antagonists transformed slow oscillations into large amplitude spike-wave discharges that contained a rhythmic ∼10 Hz neocortical oscillation. The 10 Hz oscillations caused by disinhibition were highly region specific and were generated only in frontal agranular regions of neocortex, such as the primary motor cortex, but not in granular neocortex. Pharmacological manipulations showed that the 10 Hz oscillations were critically dependent on α-amino-3-hydroxy-5-methylisoxazole-4-propionate (AMPA) receptors. Current source density (CSD) analyses in slices using 16-site silicon probes revealed that the 10 Hz oscillations were expressed with large current sinks in the upper layers and smaller current sinks in the lower layers that precede them. The results indicate that blocking GABA(B) receptors in the agranular neocortex unmasks recurrent synaptic activity mediated by AMPA receptors that results in the generation of these oscillations.